Intravascular/intralymphatic histiocytosis: A report of 3 cases - (:unkn) unknown (Lippincott Williams and Wilkins, 2015)
Intravascular/intralymphatic histiocytosis (IV/ILH) is a rare, reactive cutaneous condition, with uncertain pathogenesis. It may be associated with various inflammatory and neoplastic diseases. Although the clinical presentation is various, the biopsies reveal dilated vessels, mostly lymphatics, containing aggregates of histiocytes within their lumina. We described 3 cases of IV/ILH with different clinical presentations. In the first case, the patient presented with lymphedema in the genital region without any underlying disease. However, the second and third cases had reticular erythematous skin lesions. The second case had common variable immunodeficiency disease, rheumatoid arthritis, inflammatory bowel disease, and a history of a lymphoproliferative lesion. The third case had metal prostheses at both his right and left knees. In all these 3 cases, histopathologic and immunohistochemical findings were similar to each other and to those cases reported in the literature. In addition, the third case was admixed with reactive angioendotheliomatosis. In the second case, the endothelium of the ectatic vessels expressed CD31 and CD34, but not D2-40/podoplanin, pointing out that these vessels were blood vessels rather than lymphatics, differing from the other 2 cases. In conclusion, we believe, the most convincing statement about IV/ILH is that it is not a distinct clinicopathologic entity, but a histopathologic feature found as a part of a constellation of inflammatory changes or many other conditions. Copyright © 2015 Wolters Kluwer Health, Inc.
Keywords: Intralymphatic histiocytosis; Intravascular histiocytosis; Reactive angioendotheliomatosis